Social media usage in the framework of online public relations activities - Al-Yaqoub, Rasha Adel Ahmad (2020)
The increasing role of public relations (PR) in higher education institutions is the result of dynamic social media tools that permit participation and provide reliable and continuous access to the information. The objective of this study is to investigate the utilisation of online PR activities in Jordanian universities. In additions, the purpose of the study is to examine the antecedents of online PR and to explore its consequences from the perspectives of PR practitioners. It employed in-depth face-to-face interviews with 23 PR managers from public and private Jordanian universities based on a purposive sampling technique. The data was analysed using NVivo 12 software for content analysis via thematic analysis technique. The findings showed that the PR practitioners has conceptualised online PR as a part of the modem technology revolution, effective and sustainable in this era. They recognised the tools of the advanced technology revolution as social media vehicles and utilised Internet-based applications to spread information about their institutions. For instance, the study also found that online PR in Jordanian university was used in publishing and broadcasting, serving as a communication channel and an event platform for it students and public. The findings also discovered that technical skills, language skills, human management skills, and organisational support are antecedents of successful online PR activities. Furthermore, the cost saving, spread of information, high cost, resolvement of problems and visibility of the organisation is a consequences of online PR activities. Finally, this study contributes in developing and validating the online PR framework, which provides better guidelines for PR practitioners to apply in the context of Jordanian higher education sector.